Measurement of Practices-Knowledge-Attitudes of the Nursing Process: Systematic Review - Fabio Alberto Camargo-Figuera (Universidad de Antioquia, 2021)
Objective. To analyze the literature available on the psychometric properties of the instruments to measure knowledge, attitudes, and practices of the nursing care process.